Early Discontinuation of Antiproliferative Drugs and Application of Higher Dose Steroids Improve Prognosis of COVID-19 Infection and do not Cause Deterioration of Kidney Function in Renal Immunosuppressed Patients - Megahed, Abir Farouk; Mohamed, Dina Abouelkheir Abdalla; El-Said, Ghada; Nafel, Omar Ahmad Al; Sayed-Ahmed, Nagy (New Advances in Medicine and Medical Science Vol. 6, 2023)
Aims: Exploring whether modification of the immunosuppressive regimen in patients with renal transplantation who have active COVID-19 would improve the outcome of infection and preserve kidney function. Methods and Materials: The investigation was carried out among 18 patients (13 males and 5 females) admitted to the King Salman Specialized hospital (KSSH), a COVID-19 isolation center, in Hail city in KSA; of them, 16 had kidney transplantation maintained on immunosuppression protocols, while 2 had immune-mediated nephritis maintained on immunosuppression. The employed antivirals, anticoagulant, and immunosuppressive protocol that had been locally agreed upon were all adhered to without deviation. The following information was logged: demographics, comorbidities, baseline x-ray, standard laboratory results, and patient outcomes. Results: The patients investigated ranged in age from 23 to 60 years. Nine patients were treated in the ward (group 1), whereas the remaining nine required admission to the ICU (group 2). Group 2 patients exhibited higher mortality, higher levels of TLC, CRP, and serum phosphorus, as well as admission LDH and D-dimer than group 1. Furthermore, individuals in Group 2 exhibited lower serum albumin levels as well as lower platelet and lymphocyte counts. All patients were kept on corticosteroids and calcineurin inhibitors if they had been taking them before the infection. Antiproliferative medications (MMF or Azathioprine) were stopped in all patients; 15 ceased on the first day of admission, and 3 were hesitant to stop the drugs until they were hospitalized to the ICU a few days later. Four of the total observed patients died; three of these were those who did not discontinue these medicines early in the course of the disease. Conclusions: Increasing the dose of steroids and appropriately early discontinuation of antiproliferative drugs in renal immunosuppressed patients can be accompanied by better prognosis of COVID-19 infection patients and did not cause deterioration of kidney function.